Self-assembly and encapsulation of metal nanoparticles - Yang, Miaoxin (2011)
This thesis contains three parts. In the first part, magnetic nanoparticles (γ-Fe2O3, Fe3O4, fePt) were prepared, followed by phase-transferring into water. In presence of a hydrophobic surface ligand (2,3-naphthalenediol or oleic acid), amphiphilic block co-polymer (MagNPs) in a mixture solvent of H2O/DMF. With the help of small amount of alcohol, well-separated MagNPs can be encapsulated and separated by centrifugation. In the second part, a new type of polymer encapsulated Surface Enhanced Raman Scattering (SERS) label was developed. Au nanoparticles (AuNPs), Au nanorods (AuNRs), Ag nanoparticles (AgNPs) and Ag nanocubes (AgNCs) were prepared, on which a layer of hydrophobic Raman analytes were assembled. In presence of PS-b-PAA and water, micelles were formed around Au/Ag nanostructures. Three different molecules were used as Raman analytes and multiplexing were achieved. The polymer shell can protect the metal core from oxidation and aggregation; meanwhile provides a site for functionalization. SERS enhancement factors were estimated for different-sized Au/Ag nanoparticles. In the last part, AuNPs coated with 2- naphthalenediol were found to aggregate into linear chains in DMF/H2O mixture solutions in presence of acid (HCl) or salt (NaCl). With the help of PS-b-PAA, the linear AuNP chains can be encapsulated by forming micelles. The core shell structures can trap and retain the morphology of aggregated AuNPs at any time in solution, as well as ruling out the ambiguity caused by TEM preparation. The formation of the linear AuNPs chain was studied by TEM and UV-vis spectroscopy, and electrostatic repulsion was believed to be the main reason leading to the unique 1D aggregation.